Differences in Caregivers’ Burden in Caring for Children with Intellectual Disabilities who Attend Formal And Non-Formal Education - Suharta; Hasan Huda, Muhammad; Widianti, Wina; Setiawan, Henri (Alta Dharma Publisher, 2022)
Background: Children with Intellectual Disabilities (ID) or mental disorders caused by genetic disorders have a higher risk of morbidity and mortality than normal individuals. Long dependence causes the caregiver burden to increase. Objective: To measure the difference in caregiver burden on ID children attending formal and non-formal education. Method: The type of research used is observational analytic with a cross-sectional approach. The number of samples was 85 respondents, with 55 parents with children in formal education and 30 having non-formal education. The research instrument used the ZBI (Zarit Burden Interview) questionnaire. Statistical data were analyzed using the Mann-Whitney U Test. Results: A total of 42 (76.4%) respondents with ID children attending formal education has no burden, while 28 (93.3%) respondents with non-formal education ID children considered it moderate. Conclusion: The Mann-Whitney U Test shows a significant value of < 0.000 or < 0.05, which states that there is a significant difference between the burden of caregivers for ID children and formal and non-formal education. For future research, we recommend that the classification of formal and non-formal education be explained in more detail by involving inclusive education and home-schooling